Sex-specific incidence rates and risk factors of premature cardiovascular disease. A long term follow up of the Tehran Lipid and Glucose Study. (15th January 2017) - Eslami, Ali; Mozaffary, Amirhossein; Derakhshan, Arash; Azizi, Fereidoun; Khalili, Davood; Hadaegh, Farzad
Abstract: Objectives: To investigate the risk factors for premature cardiovascular disease (CVD) and to quantify their population attributable fractions (PAFs) among an Iranian population during a median follow-up of 12 years. Methods: A total of 2235 men and 3703 women, aged ≥ 30 years, free of CVD at baseline were entered into the study. Premature CVD was defined as having a history of CVD events before the age of 55 and 65 for men and women, respectively. Multivariate Cox proportional hazard regression models were used to determine the risk factors associated with premature CVD events. Results: During the study, incident rates of premature CVD were 4.8 and 3.9 per 1000 person years for men and women, respectively. Low HDL-C [Hazard ratio: 1.74, 95% confidence interval: 1.11–2.74], hypercholesterolemia [3.01: 2.02–4.49], current smoker [1.68: 1.12–2.51], family history of premature CVD [2.04: 1.36–3.07], hypertension [1.65: 0.97–2.81, P = 0.06] and type 2 diabetes(T2D) [1.98: 1.16–3.40] were significant predictors among men; the corresponding PAFs were 32.7, 29.4, 19.4, 14.9, 8.7 and 7.9%, respectively. Among women, T2D [3.02: 2.08–4.39], hypercholesterolemia [1.65: 1.19–2.29], being overweight [1.79: 1.01–3.17], hypertension [1.54: 1.01–2.34], family history of premature CVD [1.65: 1.19–2.29], high physical activity [0.67: 0.46–0.96] and prediabetes [1.48: 1.00–2.18] were significant predictors; the corresponding PAFs were 25.4, 22.5, 18.5, 16.8, 11.4, − 10.3 and 9.1%, respectively. Conclusions: Considering the high burden imposed on health system by cardio-metabolic risk factors, dietary, behavioral and pharmacological interventions are need to be initiated early to prevent premature CVD, taking into account the sex-related differences between risk factors.